SOCIAL MEDIA AS A TOOL FOR TOURISM PROMOTION POST PANDEMIC WORLD (International Journal of Food and Nutritional Sciences, 2022)
Nowadays it’s completely impossible to imagine the world without Social Media as it has inculcated as a daily routine of our lives. Apart from other forms of business, the Tourism sector has been greatly influenced. Due to Covid -19 the tourism sector had been worst affected. This paper attempts to establish how Social Media can be used a means of revival and uplift and regenerate the importance of travel back in the lives of travellers. Hotels, airlines, railways, and other tourist operators are all adopting various safety and hygiene regulations and practices, to revive the tourism spirit in human society. Social Media is one the prominent tools which havegained a lot of potentiality for reshaping the way human society and industry works and to revitalize the tourism sector as well. WOM, UGM, cross referencing, and social media together are proving to be a great help.Sherry Thomas (September 2016) observed that human urge for communicating, and the advancements in digital media, have fueled emergence of social media. With driven by digital information sharing to virtual meeting places, retail platforms, and essential 21st-century marketing tools, social media has revolutionized in less than decade and hence, connecting individuals from different corners of the world.